Biomimetic scaffolds for bone tissue engineering - Park, Joon Yeong; Park, Seung Hun; Kim, Mal Geum; Park, Sang Hyug; Yoo, Tae Hyeon; Kim, Moon Suk (Advances in Experimental Medicine and Biology, 2018)
The use of biomimetic scaffolds for bone tissue engineering has been studied for a long time. Biomimetic scaffolds can assist and accelerate bone regeneration that is similar to that of authentic tissue, which represents the environment of cells in a living organism. Currently, numerous biomaterials have been reported for use as a biomimetic scaffold. This review focuses on the design of biomimetic scaffolds, kinds of biomaterials and methods used to fabricate biomimetic scaffolds, growth factors used with biomimetic scaffold for bone regeneration, mobilization of biological agents into biomimetic scaffolds, and studies on (pre)clinical bone regeneration from biomimetic scaffolds. Then, future prospects for biomimetic scaffolds are discussed.
Keywords: Biomimetic Materials; Bone and Bones; Bone Regeneration; Humans; Tissue Engineering; Tissue Scaffolds; Biomaterial; Biomimetic scaffold; Bone regeneration; Tissue engineering